FIGURATIVE LANGUAGES IN BTS SONGS LYRIC’S - Nurwahida Nurwahida; Yunitari Mustikawati (Faculty of Languages and Literature, Universitas Negeri Makassar, 2022)
Figurative language was a way of expressing feelings, thoughts, and ideas. The song lyrics analyzed by the researcher were: Louder than Bombs, Spring Day, Butter, Dynamite, 00:00 (zero o'clock), Fake Love, and Magic Shop. Figurative language in this study used the theory of X.J Kennedy and message theory by several experts and sources. This researcher used the descriptive qualitative method. Lyrics is an expression that songwriter feels to describe an object or experience. In this study, researcher found 11 kinds of figurative language in BTS song lyrics, namely: personification, metaphor, simile, hyperbole, paradox, irony, metonymy, synecdoche, symbol, allusion, and repetition. The most dominant figurative language is simile. Thus, researcher found 22 messages through figurative language in BTS songs, in the Louder than Bombs song messages is everyone is good at hiding sadness, In the Spring Day song messages is expectations and reality. In the Butter song messages, is keep trying to get you want, The Dynamite song messages is fun has no limit. In the 00:00 (Zero O'clock) song messages is don’t stop praying for happiness. In the Fake Love song messages is loving ourselves is much more fun, In the Magic Shop song messages is never give up on our own life.